Pediatric acute-onset neuropsychiatric syndrome and pediatric autoimmune neuropsychiatric disorder associated with streptococcal infections: a delphi study and consensus document about definition, diagnostic criteria, treatment and follow-up - Grandinetti, Roberto; Mussi, Nicole; Pilloni, Simone; Ramundo, Greta; Miniaci, Angela; Turco, Emanuela; Piccolo, Benedetta; Capra, Maria Elena; Forestiero, Roberta; Laudisio, Serena; Boscarino, Giovanni; Pedretti, Laura; et al. (Frontiers in Immunology, 2024)
Pediatric Autoimmune Neuropsychiatric Disorder Associated with Streptococcal Infections (PANDAS) and Pediatric Acute-onset Neuropsychiatric Syndrome (PANS) are broad diagnoses that encompass a range of sudden-onset neuropsychiatric symptoms in children, which can include obsessive-compulsive disorder (OCD), tics, anxiety, emotional instability, and cognitive difficulties.Unlike PANDAS, PANS is not strictly linked to group A streptococcal infections but can be triggered by various infectious or environmental factors. Lights and shadows remain upon the management of children with PANS and PANDAS and there is no clear consensus regarding definition, diagnostic criteria, treatment, and follow-up. The aim of the present study was to evaluate the level of agreement on PANS and PANDAS definition, diagnostic criteria, treatment and follow-up and to assess on the basis of recent studies whether there is a need to modify the current recommendations used by primary care pediatricians and hospital pediatricians in clinical practice in order to improve outcomes. Using the Delphi method, this consensus provides shared indications on PANS and PANDAS management in pediatric age, based on the most updated literature. This work represents, in our opinion, the most complete and up-to-date information on the diagnosis of PANS and PANDAS, as well as consensus statements about several aspects of clinical care. Undoubtedly, more randomized and controlled trials are needed in the pediatric population to better define the best management, also in terms of adequate follow-up examinations and period of observation.